A Facile Synthesis of Ligands for the von Hippel–Lindau E3 Ligase - Steinebach, Christian; Voell, Sabine Anna; Vu, Lan Phuong; Bricelj, Aleša; Sosič, Izidor; Schnakenburg, Gregor; Gütschow, Michael (Synthesis, 2020)
The proteolysis-targeting chimeras (PROTACs) have become an integral part of different stages of drug discovery. This growing field, therefore, benefits from advancements in all segments of the design of these compounds. Herein, an efficient and optimized synthetic protocol to various von Hippel-Lindau (VHL) ligands is presented, which enables easy access to multigram quantities of these essential PROTAC building blocks. Moreover, the elaborated synthesis represents a straightforward approach to further explore the chemical space of VHL ligands.
Keywords: PROTACs; protein degradation; von Hippel–Lindau; VHL; E3 ligase; reductive amination; protecting group